2021
DOI: 10.1136/thoraxjnl-2020-216244
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of genetic and clinical screening for pulmonary fibrosis on asymptomatic first-degree relatives of affected individuals

Abstract: Screening for pulmonary fibrosis may help to identify early stages of the disease. We assessed the psychological impact of screening undiagnosed first-degree relatives of patients with pulmonary fibrosis by administering two validated measures after participants received their results: the Decisional Regret Scale and the Feelings About genomiC Testing Results Questionnaire. More than 90% of relatives reported either no or mild decisional regret. Increased measures of decisional regret and negative feelings wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…25 It has been shown that most relatives of patients with pulmonary fibrosis have no major concerns with screening for early disease by means of genetic testing. 27 However, if relatives received abnormal imaging or pulmonary function test results, more regret and other negative feelings were experienced. 27 Thus, appropriate counselling, but also expert medical advice are of crucial importance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 It has been shown that most relatives of patients with pulmonary fibrosis have no major concerns with screening for early disease by means of genetic testing. 27 However, if relatives received abnormal imaging or pulmonary function test results, more regret and other negative feelings were experienced. 27 Thus, appropriate counselling, but also expert medical advice are of crucial importance.…”
Section: Discussionmentioning
confidence: 99%
“…27 However, if relatives received abnormal imaging or pulmonary function test results, more regret and other negative feelings were experienced. 27 Thus, appropriate counselling, but also expert medical advice are of crucial importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This impact may not always be negative, and in fact some patients may be relieved by knowing their genetic status. Encouragingly, Carmichael et al 80 found that relatives of patients with pulmonary fibrosis who underwent clinical and genetic screening did not experience excessive decisional regret, but there are still many unknowns about the potential psychological ramifications of genetic testing that require exploration. Given the nuances and potential pitfalls of genetic testing, we recommend referring patients with FPF to certified genetic counselors who can offer invaluable insight through pretesting counseling, choosing the appropriate genetic test, interpreting the results, and providing posttesting counseling to patients and their relatives.…”
Section: Clinical Genetic Testing Considerationsmentioning
confidence: 99%
“…There are many reasons why the identification of causative TCG variants in patients with IPF is important from a clinical standpoint. Firstly, it offers the possibility of genetic counseling [22,25]. Secondly, it influences the prognosis [26,27] (i.e., after lung transplantation) and can have an impact on treatment decisions [28,29] (i.e., treatment adjustments after lung transplantation).…”
Section: Introductionmentioning
confidence: 99%